2016
DOI: 10.1016/j.jamcollsurg.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Is Preoperative Axillary Imaging Beneficial in Identifying Clinically Node-Negative Patients Requiring Axillary Lymph Node Dissection?

Abstract: Background ACOSOG Z0011 results support the omission of axillary lymph node dissection (ALND) in women with <3 positive sentinel lymph nodes (SLNs) undergoing breast-conserving surgery (BCS) and radiation therapy. We sought to determine if abnormal axillary imaging is predictive of the need for ALND in this population. Study Design Patients with cT1-2N0 breast cancer by physical examination undergoing BCS were managed according to Z0011 criteria independent of axillary imaging. Patient characteristics and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 26 publications
1
37
0
1
Order By: Relevance
“…We have previously published on rates of ALND among women with cN0 disease with abnormal axillary imaging when treated according to Z0011 and found that ALND was only required in 30% of those with an abnormal axillary ultrasound. 27 This is in contrast to data published by Barrio et al 28 who reported on cN0 patients with abnormal axillary imaging who underwent NAC and found that 40% of those with an upfront abnormal axillary ultrasound required ALND post-NAC. In addition, 23% of women who were cN0 without abnormal axillary imaging prior to NAC were pathologically node positive following NAC.…”
Section: Discussionmentioning
confidence: 70%
“…We have previously published on rates of ALND among women with cN0 disease with abnormal axillary imaging when treated according to Z0011 and found that ALND was only required in 30% of those with an abnormal axillary ultrasound. 27 This is in contrast to data published by Barrio et al 28 who reported on cN0 patients with abnormal axillary imaging who underwent NAC and found that 40% of those with an upfront abnormal axillary ultrasound required ALND post-NAC. In addition, 23% of women who were cN0 without abnormal axillary imaging prior to NAC were pathologically node positive following NAC.…”
Section: Discussionmentioning
confidence: 70%
“…21 However, the role of axillary imaging in cN0 patients meeting ACOSOG Z0011 criteria has been questioned. We have previously demonstrated that the identification of abnormal nodes on preoperative imaging 22 or even a positive needle biopsy 23 does not reliably identify a group of patients who require ALND when ACOSOG Z0011 eligibility criteria are otherwise met. While BMI has been not been shown to impact the sensitivity of axillary ultrasound 24-26 , our data suggest that obesity itself is not an indication for additional axillary evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a judicious use of, as well as interpretation of, US-guided axillary staging is required when deciding on the surgical management of the axilla. As established by the ACOSOG Z0011 trial, further treatment is not required in certain patients with one or two positive axillary nodes, and the mere presence of abnormal nodes on imaging in clinically node-negative patients is not a reliable indicator of the need for ALND (12). …”
Section: Invasive Breast Cancer Clinically Node Positivementioning
confidence: 99%